A Automatic Box Folding Machine - Misman, Dalila; Nagulan, Naveeshvaran (Progress in Engineering Application and Technology, 2020)
A PLC is a programmable logic controller which is a type of industrial controller. This paper represents based on graduation project; a simulation and prototype in which a carton box enters a folding machine and automatically folded at lower part. We have used various components in this project such as 12V power supply, 24V power supply, main switch, start push button, stop push button, sensors and DC motor. All these components are controlled using PLC. The main aim of this project is to reduce time, manpower, more efficient folded box. In this automatic box folding machine project we use the main switch for safety.. Firstly, we take main switch and start push button on when the folding machine is turn on to pass first photo sensor senses carton box after entered manually, box holder will go down to folder arm, box fold the lower part step by step which is left, right, front, and back according to time given. The first author will mainly carried out of designing, implementation and analysis of “Automatic box folding machine”